A new social contract inclusive of informal workers - Martha Alter Chen; Sophie Plagerson; Laura Alfers (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
This paper makes the case that current social contracts are often inadequate, irrelevant, or unjust for informal workers. It outlines three possible future scenarios: the bad old contract, an even worse contract, and a better new contract. Under the bad old contract, informal workers lacked legal recognition, were stigmatized and penalized, and were excluded as partners. The intensification of predatory capitalism, repressive state policies and the collusion of state and capital, in the wake of the COVID-19 pandemic recession, makes the possibility of a worse new deal all too real. The key changes needed for a better new contract are a change in mindsets and dominant narratives that stigmatize the informal economy and the inclusion of informal workers as key partners. The key features of a better new deal are recognition, responsiveness, and reciprocity, between state, capital, and informal labour (the majority of workers globally).
Keywords: J46; 330; informal workers; informal economy; social contracts; state and capital